Multi-omics analysis reveals CLIC1 as a therapeutic vulnerability of gliomas - Wang, Chengcheng; He, Zheng (Frontiers in Pharmacology, 2023)
Despite advances in comprehending cancer biology, malignant gliomas remain incurable. The present work conducted a multi-omics analysis for investigating the significance of chloride intracellular channel 1 (CLIC1) in gliomas. Multi-omics data of glioma covering transcriptomics, genomics, DNA methylation and single-cell transcriptomics from multiple public cohorts were enrolled for analyzing CLIC1. In vitro experiments were conducted to measure apoptosis and cell mobility in U251 and U373 glioma cells following transfection of CLIC1 siRNAs. Elevated CLIC1 expression was proven to stably and independently estimate worse survival outcomes. CLIC1 expression was higher in more advanced stage, wild-type IDH and unmethylated MGMT samples. Tumorigenic and anticancer immunity pathways were remarkably enriched in CLIC1-up-regulated tumors. Additionally, CLIC1 was positively linked with cancer-immunity cycle, stromal activation, DNA damage repair and cell cycle. Suppressing CLIC1 resulted in apoptosis and attenuated cell motility of glioma cells. More frequent genomic alterations were found in CLIC1-up-regulated tumors. CLIC1 expression presented a remarkably negative connection to DNA methylation. High CLIC1 expression samples were more sensitive to camptothecin, cisplatin, doxorubicin, erlotinib, paclitaxel, rapamycin, clofarabine, tanespimycin, methotrexate, everolimus, TAK-733, trametinib and AZD8330. Tumors with up-regulated CLIC1 presented abundant immune cell infiltration, higher expression of immune-checkpoints and -modulators and similar transcriptome profiling, indicative of well response to immune-checkpoint blockade (ICB). Nevertheless, due to elevated TIDE score, tumors with CLIC1 up-regulation appeared to be resistant to ICB. Single-cell analysis unveiled that CLIC1 was expressed ubiquitously in tumor cells and tumor microenvironment. Overall, CLIC1 was a promising treatment vulnerability in glioma.